Novel method for the synthesis of siloxane nanowires and filaments using gold nanoparticle catalysts - Bhagavatula L. V. Prasad; Stoeva, S.; Sorensen, C. M.; Klabunde, Kenneth J.; Zaikovskii, V. (International Conference on Nanoscience and Technology, 2005)
A unique polymerization reaction of alkylsilanes to siloxane nanowires, filaments and tubes in presence of gold nanoparticles and water is presented. The gold nanoparticles, which catalyze this reaction also work as templates restricting the shape of the resulting polymers into wires and tubes. High resolution transmission electron microscopy images clearly reveal the presence of gold nanoparticle at the tip of each wire supporting the template hypothesis. Elemental analyses by different methods confirm the stoichiometry to be C18H37SiO1.5, when the alkylsilane used was C18H37SiH3, thus proving that the alkyl group remains intact during the polymerization reaction.
Keywords: gold nanoparticles; Nanowires; siloxane polymers

Reversible transformations of gold nanoparticle morphology - Stoeva, Savka I.; Zaikovski, Vladimir; Bhagavatula L. V. Prasad; Stoimenov, Peter K.; Sorensen, Christopher M.; Klabunde, Kenneth J. (Langmuir, 2005)
Herein is reported a metamorphosis taking place in a gold nanosized system. The observed phenomenon of shape and size transformations was found to be completely reversible. Unlike most procedures in the literature where shape and size control occur in the synthetic step by adding growth- and shape-controlling agents such as surfactants or polymers, in this system postsynthetic changes in shape and size can be carried out simply by changing the ratio of reactive, competing reagents, more specifically, alkylthiols versus tetralkylammonium salts. Interestingly, the transfer of gold metal occurs (large prismatic particles to small particles and vice versa) under the influence of reagents that do not cause such interactions with bulk gold. All intermediate steps of the morphology change were observed using HRTEM and electron diffraction. The processes of breaking down and “welding back” solid metal nanoparticles occur under mild conditions and are remarkable examples of the unique chemical properties of nanomaterials. The described process is expected to be relevant to other nanoscale systems where similar structural circumstances could occur.

Gold nanoparticle superlattices - Bhagavatula L. V. Prasad; Sorensen, C. M.; Klabunde, Kenneth J. (Chemical Society Reviews, 2008)
Ordered metal nanoparticle assemblies-superlattices-have captivated and stirred the imagination of scientists and engineers alike and promise great prospect for future technologies. This potential though will greatly be determined by the understanding and control that can be exerted on the assembling processes. This tutorial review presents a brief account of the factors that govern the formation of superlattices and then presents several examples of gold nanoparticle superlattices that are distinguished by the size of participating particles, chain length/functional group of the capping agent, the substrates on which they form etc.